Optimum range of angle tracking radars: a theoretical computing - Sadegh Samadi; Mohammad Reza Khosravi; Jafar A. Alzubi; Omar A. Alzubi; Varun G. Menon (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, we determine an optimal range for angle tracking radars (ATRs) based on evaluating the standard deviation of all kinds of errors in a tracking system. In the past, this optimal range has often been computed by the simulation of the total error components; however, we are going to introduce a closed form for this computation which allows us to obtain the optimal range directly. Thus, for this purpose, we firstly solve an optimization problem to achieve the closed form of the optimal range (Ropt.) and then, we compute it by doing a simple simulation. The results show that both theoretical and simulation-based computations are similar to each other.